Reevaluation of taxonomic identity of the recently introduced invasive planthopper, Pochazia shantungensis (Chou & Lu, 1977) (Hemiptera: Fulgoroidea: Ricaniidae) in Japan - Kobayashi, Shigeki; Suzuki, Masahiro; Kuwahara, Ryosuke; Park, Jaekook; Yamada, Kazutaka; Jung, Sunghoon (Zootaxa, 2024)
The taxonomic identity of the invasive Asian Ricaniid planthopper, Pochazia shantungensis (Chou & Lu, 1977) in Japan is reevaluated. This originally Chinese planthopper is highly polyphagous and has recently become an important pest in Korea. In 2015, this species was first documented from Sakai, Osaka Prefecture and has been widespread since then. The genital structures, wings and fifth instar nymph are described and illustrated. The host plants in Japan are also documented with photographs. The male genitalia of a similar species, P. sublimata (Jacobi, 1916), are illustrated as well. As a recently introduced pest in Japan, P. shantungensis needs to be monitored for its potential spread and for the damage it may cause to agriculture.